The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.13045/jar.2022.00087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Facial Chuna Manual Therapy Combined with Korean Medicine Treatmeant for Bell’s Palsy

Abstract: The effect of combined Korean medicine treatment including facial chuna manual therapy was retrospectively investigated in patients with Bell’s palsy. There were 16 patients (14 males) who received 2 months outpatient treatment following > 14 days of hospitalization. The Yanagihara score and House- Brackmann grade were used to measure the severity of symptoms and recovery. The patients (mean age 58.5 ± 24.74 years) were categorized based on their medical history of hypertension (n = 10), diabetes millitus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, a study [16] reported that SJS non-resistance technique-facial palsy manual therapy based on the restoration of muscle nerves by re-education of the paralyzed muscles was effective in cases that were not responsive to conventional KM treatment such as acupuncture and EA. Recently, some studies [17,18] have analyzed the effects of K-FCMT combined with conventional KM treatment on patients with Bell's palsy in the plateau phase and sequelae phase.…”
Section: Jarmentioning
confidence: 99%
“…Moreover, a study [16] reported that SJS non-resistance technique-facial palsy manual therapy based on the restoration of muscle nerves by re-education of the paralyzed muscles was effective in cases that were not responsive to conventional KM treatment such as acupuncture and EA. Recently, some studies [17,18] have analyzed the effects of K-FCMT combined with conventional KM treatment on patients with Bell's palsy in the plateau phase and sequelae phase.…”
Section: Jarmentioning
confidence: 99%